Pengembangan E-book Digital sebagai Media Pembelajaran untuk Meningkatkan Literasi Digital Peserta Didik Kelas XI SMK Negeri 2 Surabaya: Pengembangan E-book Digital sebagai Media Pembelajaran untuk Meningkatkan Literasi Digital Peserta Didik Kelas XI SMK Negeri 2 Surabaya - LAILA VIKA SAFITRI VIKA; HARMANTO HARMANTO; OKSIANA JATININGSIH (Universitas Negeri Surabaya (Unesa), 2026)
This research aims to develop digital e-book learning media on the meaning of the motto Bhinneka Tunggal Ika for grade XI students at SMK Negeri 2 Surabaya. The research problem was identified through field observations and interviews, which showed that learning was still dominated by lecture methods using conventional teaching materials, causing students to have difficulty understanding the philosophical meaning of the Bhinneka Tunggal Ika motto in context. This study used the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model, involving 35 students in class XI RPL 2 as test subjects. Data collection was conducted through observation, interviews, teacher validation questionnaires, and student response questionnaires. The results showed that the developed digital e-book obtained a teacher validation score of 90.67% in the “Highly Valid” category, meeting the eligibility standards in terms of material suitability, content accuracy, presentation systematics, visual appearance, language, and media usability in learning. Meanwhile, student responses to the digital e-book showed an average score of 78.33% in the “Valid” category, indicating that this learning medium is effective, interesting, easy to use, and helps students understand the meaning of the Bhinneka Tunggal Ika motto through the integration of multimedia and contextual interactive features. This digital e-book also makes a significant contribution.